A case of slowly progressive malignant pericardial mesothelioma suggesting the involvement of BAP1 loss. Issue 9 (6th August 2022) - Fukasawa, Naoto; Agemi, Yoko; Shiba, Aya; Aga, Masaharu; Hamakawa, Yusuke; Miyazaki, Kazuhito; Taniguchi, Yuri; Misumi, Yuki; Shimokawa, Tsuneo; Ono, Kyoko; Hayashi, Hiroyuki; Okamoto, Hiroaki
Abstract: Malignant pericardial mesothelioma (MPM) is a rare tumour that arises from the mesothelial cells of the pericardium. No standard treatment has been established owing to a poor treatment response; therefore, MPM has a poor prognosis. We herein report a rare case of MPM in a 70‐year‐old man that was diagnosed immunohistopathologically using cell block sections of pericardial fluid and in which long‐term survival for more than 3 years was achieved with only periodic pericardial drainage. Immunohistopathological staining investigations, especially BRCA1‐associated protein 1 (BAP1) immunostaining using cell block sections of pericardial effusion, are effective in making a diagnosis of MPM. Well‐differentiated papillary mesothelioma (WDPM) with BAP1 loss progresses to MPM in the long term, showing that BAP1 loss may induce phenotypical evolution of WDPM. BAP1 loss may also progress to malignant mesothelioma in situ and then to invasive mesothelioma. BAP1 immunohistochemistry should be considered for the early diagnosis of MPM. Abstract : We report a rare case of malignant pericardial mesothelioma diagnosed immunohistopathologically using cell block sections of pericardial fluid and the patient had prolonged survival for more than 3 years with only periodic pericardial drainage.